DNA methylation changes in genes frequently mutated in sporadic colorectal cancer and in the DNA repair and Wnt/β-catenin signaling pathway genes - Farkas, Sanja A; Vymetálková, Veronika; Vodičková, Ludmila; Vodička, Pavel; Nilsson, Torbjörn K (Epigenomics, 2014)
AIM: The onset and progression of colorectal cancer (CRC) involves a cascade of genetic and/or epigenetic events. The aim of the present study was to address the DNA methylation status of genes relevant in colorectal carcinogenesis and its progression, such as genes frequently mutated in CRC, genes involved in the DNA repair and Wnt signaling pathway. MATERIAL & METHODS: We analyzed methylation status in totally 160 genes in 12 paired colorectal tumors and adjacent healthy mucosal tissues using the Illumina Infinium Human Methylation 450 BeadChip. RESULTS: We found significantly aberrant methylation in 23 genes (NEIL1, NEIL3, DCLRE1C, NHEJ1, GTF2H5, CCNH, CTNNB1, DKK2, DKK3, FZD5 LRP5, TLE3, WNT2, WNT3A, WNT6, TCF7L1, CASP8, EDNRB1, GPC6, KIAA1804, MYO1B, SMAD2 and TTN). External validation by mRNA expression showed a good agreement between hypermethylation in cancer and down-regulated mRNA expression of the genes EDNRB1, GPC6 and SMAD2, and between hypomethylation and up-regulated mRNA expression of the CASP8 and DCLRE1C genes. CONCLUSION: Aberrant methylation of the DCLRE1C and GPC6 genes are presented here for the first time and are therefore of special interest for further validation as novel candidate biomarker genes in CRC, and merit further validation with specific assays.
Keywords: Gene Expression Regulation, Neoplastic; DNA Methylation; RNA, Messenger; Male; kolorektální nádory; Wnt Signaling Pathway; Endonucleases; metylace DNA; Glypicans; beta Catenin; regulace genové exprese u nádorů; epigeneze genetická; CpG ostrůvky; Aged; jaderné proteiny; promotorové oblasti (genetika); mužské pohlaví; senioři; proteiny Wnt; lidé středního věku; Wnt Proteins; DNA Repair; oprava DNA; endonukleasy; lidé; ženské pohlaví; Humans; Promoter Regions, Genetic; Colorectal Neoplasms; CpG Islands; signální dráha Wnt; Female; Nuclear Proteins; messenger RNA; glypikany; beta-katenin; Epigenesis, Genetic; Middle Aged